Penerapan Resirkulasi Akuarium Modular terhadap Peningkatan Kualitas Karang Hias (Corals) di CV. Rezky Bahari Sulawesi Selatan - Irmawati Irmawati; Ratnawati Ratnawati; Mauli Kasmi (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to determine the application of modular aquarium recirculation to improving the quality of ornamental corals at CV. Rezky Bahari, South Sulawesi. As for the application of modular aquarium recirculation at CV. Rezky Bahari is that it has been implemented and runs according to its function or use and can improve the quality of ornamental corals in the company. This research uses quantitative and qualitative descriptive data analysis methods. The samples used were all the number of ornamental corals found in 5 modular aquariums..The results of the study were obtained by making direct observations about how changes before and after recirculation was applied. With this direct observation, it has been proven that the quality of ornamental corals is very influential on the application of recirculation where there are many changes ranging from the level of survival to the quality of water.